2014
DOI: 10.1016/j.tvjl.2014.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic features of feline sino-nasal and sino-orbital aspergillosis

Abstract: Makara, M. (2014). Computed tomographic features of feline sino-nasal and sino-orbital aspergillosis. Vet J. 201(2):215-22. DOI:10.1016DOI:10. /j.tvjl.2014 Computed tomographic features of feline sino-nasal and sino-orbital aspergillosis AbstractFeline upper respiratory tract aspergillosis (URTA) occurs as two distinct anatomic forms, sinonasal aspergillosis (SNA) and sino-orbital aspergillosis (SOA). An emerging pathogen, Aspergillus felis is frequently involved. The pathogenesis of URTA, in particular, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 38 publications
1
47
0
1
Order By: Relevance
“…A sinonasal origin is suspected, however, as CT findings showed the epicenter of abnormal soft tissue accumulation and bony lysis to be the nasal cavity and the paranasal sinuses. In a number of retrospective studies published in the veterinary literature reporting on various aspects of feline sinonasal disease, no single case of feline sinonasal adenosquamous carcinoma was reported. In all of these studies, tumors of nonepithelial origin (comprising mostly of lymphoma) were found to be the most common feline sinonasal neoplasm; this was followed by tumors of epithelial origin (most commonly adenocarcinoma, squamous cell carcinoma, undifferentiated carcinoma) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A sinonasal origin is suspected, however, as CT findings showed the epicenter of abnormal soft tissue accumulation and bony lysis to be the nasal cavity and the paranasal sinuses. In a number of retrospective studies published in the veterinary literature reporting on various aspects of feline sinonasal disease, no single case of feline sinonasal adenosquamous carcinoma was reported. In all of these studies, tumors of nonepithelial origin (comprising mostly of lymphoma) were found to be the most common feline sinonasal neoplasm; this was followed by tumors of epithelial origin (most commonly adenocarcinoma, squamous cell carcinoma, undifferentiated carcinoma) .…”
Section: Discussionmentioning
confidence: 99%
“…None of the cases of sinonasal neoplasia in these two studies were reported to involve skeletal structures outside of the sinonasal and paranasal region. In two studies focusing on fungal rhinosinusitis in cats, authors of both studies concluded there were many similarities in the CT appearance between sinonasal neoplasia and fungal rhinosinusitis. In their cases of feline fungal rhinosinusitis, common CT findings included development of a soft tissue mass in the nasal cavity, frontal sinus, sphenoid sinus, or nasopharynx; osteolysis affecting the turbinates, palatine bone, nasal septum, maxilla, orbital laminae, frontal bone, and cribriform plate; and extension of disease into paranasal and orbital tissues .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although aspergillosis is much less common in mammals compared with birds, similar diagnostic imaging modalities have been employed in canine patients for the diagnosis of aspergillosis, including rhinoscopy, radiography, CT, and MRI . MRI and CT use in feline patients has also been documented, and endoscopic examination of the guttural pouch and radiography have been reported in horses . As for clinical observations, definitive diagnoses by imaging is not possible, but serves as an indication that an infection is present and further analysis by more conclusive methods is required, such as identification of the microorganism using fungal cultures (Table ).…”
Section: Conventional and Digital Radiography Endoscopy And Advancementioning
confidence: 99%
“…New information on feline fungal infections is included, specifically in a report on a novel study that used computed tomography to investigate sino-nasal and sino-orbital aspergillosis (Barrs et al, 2014). Feline upper respiratory tract aspergillosis is a very topical area and this article reports infections caused by the emerging pathogen, Aspergillus felis, as well as four other Aspergillus species that have not previously been reported at this anatomical site in cats.…”
Section: Introductionmentioning
confidence: 99%